Analisis Terhadap Penafsiran Imam Al-Alusy tentang Jin, Iblis, dan Setan - Nuramin Nuramin (Jurnal Iman dan Spiritualitas, 2021)
Jinn, devils, and demons are creatures of God who are invisible or unseen. Allah created them as a sign that apart from humans, supernatural beings surround them and watch their movements from any direction they want. The three magical beings are believed to exist by all humanity. Belief in supernatural beings is an identity of faith that Muslims must possess; even Allah has confirmed it that among the characteristics of people who fear Allah are faith in the unseen, as stated in the letter Al-Baqarah verse 3, which reads: "Those who believe in the unseen". However, faith in supernatural beings does not mean we have to cult them and even worship them like God. Faith in supernatural beings is only a reflection for us that Allah can create whatever He wants and that the creatures He makes them very diverse. These are all proofs of the greatness of Allah SWT. In the Qur'an, many stories are told of jinn, devils, and demons whose purpose is none other than so that humans can take a lot of wisdom and ibrah from these stories. Many people try to explore and observe the verses about them so that many debates from them give rise to various understandings and trigger disagreements. The object of research is an invisible creature, so, understandably, there will be a lot of debate going on.